Transition metal-mediated oxidations utilizing monomeric iodosyl- and iodylarene species; Tetrahedron; Vol. 66, iss. 31 - Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Nemykin V. N.; Zhdankin V. V. Viktor Vladimirovich (2010, 2010)
Title screen